Hidden costs of energy : unpriced consequences of energy production and use - National Research Council (U.S.). Committee on Health, Environmental, and Other External Costs and Benefits of Energy Production and Consumption; National Research Council (U.S.). Board on Environmental Studies and Toxicology; National Research Council (U.S.). Board on Energy and Environmental Systems; National Research Council (U.S.). Board on Science, Technology, and Economic Policy; National Academies Press (U.S.) (Washington, D.C. : National Academies Press)
Includes bibliographical references